If y(t) is a solution of $\left( {1 + t} \right)\dfrac{{dy}}{{dt}} - ty = 1$ and $y\left( 0 \right) = - 1$, then y(1) equal to
$
(a){\text{ }}\dfrac{{ - 1}}{2} \\
(b){\text{ e + }}\dfrac{1}{2} \\
(c){\text{ e - }}\dfrac{1}{2} \\
(d){\text{ }}\dfrac{1}{2} \\
$
Answer
Verified
510.6k+ views
Hint: In this question we have to solve the given differential equation, converting this into standard differential form of $\dfrac{{dy}}{{dx}} + py = q$ and then using the concept of $y\left( {I.F} \right) = \int {\left( {I.F} \right)qdx} $ Where I.F is $ = {e^{\int {pdx} }}$ will help in getting the solution of this differential equation. Then simple substitution of 1 in place of x will help in getting the value of y(1).
Complete step-by-step answer:
The given differential equation is
$\left( {1 + t} \right)\dfrac{{dy}}{{dt}} - ty = 1$
Divide by (1 + t) in above equation we have,
$\dfrac{{dy}}{{dt}} - \dfrac{t}{{\left( {1 + t} \right)}}y = \dfrac{1}{{\left( {1 + t} \right)}}$
Now the general differential equation is $\dfrac{{dy}}{{dx}} + py = q$, the solution of this differential equation is,
$y\left( {I.F} \right) = \int {\left( {I.F} \right)qdx} $ Where I.F is$ = {e^{\int {pdx} }}$.
Now in above equation $p = \dfrac{{ - t}}{{1 + t}}$ and $q = \dfrac{1}{{1 + t}}$.
So, first calculate integrating factor (I.F)
$ \Rightarrow I.F = {e^{\int {\dfrac{{ - t}}{{1 + t}}dx} }}$
$ \Rightarrow I.F = {e^{\int {\left( {\dfrac{1}{{1 + t}} - 1} \right)dx} }}$
Now integrate it as we know $\dfrac{1}{{1 + t}}$ integration is log (1 + t) so, apply this,
$ \Rightarrow I.F = {e^{\log \left( {1 + t} \right) - t}}$
$ \Rightarrow I.F = {e^{\log \left( {1 + t} \right)}}.{e^{ - t}}$
Now as we know ${e^{\log a}} = a$ so, use this property we have,
$ \Rightarrow I.F = \left( {1 + t} \right){e^{ - t}}$
So, the solution of the differential equation is
\[y\left( {I.F} \right) = \int {\left( {I.F} \right)qdt} \]
$
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = \int {\left( {1 + t} \right){e^{ - t}}\dfrac{1}{{1 + t}}dt} \\
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = \int {{e^{ - t}}dt} \\
$
Now as we know integration of $\int {{e^{ - t}}} = \dfrac{{{e^{ - t}}}}{{ - 1}} + c$ so use this in above equation we have
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = \dfrac{{{e^{ - t}}}}{{ - 1}} + c\] (Where c is some arbitrary integration constant)
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} + c\]……………… (1)
Now it is given that $y\left( 0 \right) = - 1$
So substitute t = 0 and y = -1 in above equation we have,
$
\Rightarrow \left( { - 1} \right)\left( {1 + 0} \right){e^{ - 0}} = - {e^0} + c \\
\Rightarrow - 1 = - 1 + c \\
\Rightarrow c = 0 \\
$
Therefore from equation (1) we have
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} + 0\]
\[
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} \\
\Rightarrow y\left( {1 + t} \right) = - 1 \\
\Rightarrow y\left( t \right) = \dfrac{{ - 1}}{{1 + t}} \\
\]
Now we have to find out the value of y(1)
So put t = 1 in above equation we have,
\[ \Rightarrow y\left( 1 \right) = \dfrac{{ - 1}}{{1 + 1}} = \dfrac{{ - 1}}{2}\]
Hence option (a) is correct.
Note: Whenever we face such types of problems the key concept is to convert the differential equation into standard form in order to evaluate the integrating factor. The integration factor will help us obtain the solution required for the given differential equation.
Complete step-by-step answer:
The given differential equation is
$\left( {1 + t} \right)\dfrac{{dy}}{{dt}} - ty = 1$
Divide by (1 + t) in above equation we have,
$\dfrac{{dy}}{{dt}} - \dfrac{t}{{\left( {1 + t} \right)}}y = \dfrac{1}{{\left( {1 + t} \right)}}$
Now the general differential equation is $\dfrac{{dy}}{{dx}} + py = q$, the solution of this differential equation is,
$y\left( {I.F} \right) = \int {\left( {I.F} \right)qdx} $ Where I.F is$ = {e^{\int {pdx} }}$.
Now in above equation $p = \dfrac{{ - t}}{{1 + t}}$ and $q = \dfrac{1}{{1 + t}}$.
So, first calculate integrating factor (I.F)
$ \Rightarrow I.F = {e^{\int {\dfrac{{ - t}}{{1 + t}}dx} }}$
$ \Rightarrow I.F = {e^{\int {\left( {\dfrac{1}{{1 + t}} - 1} \right)dx} }}$
Now integrate it as we know $\dfrac{1}{{1 + t}}$ integration is log (1 + t) so, apply this,
$ \Rightarrow I.F = {e^{\log \left( {1 + t} \right) - t}}$
$ \Rightarrow I.F = {e^{\log \left( {1 + t} \right)}}.{e^{ - t}}$
Now as we know ${e^{\log a}} = a$ so, use this property we have,
$ \Rightarrow I.F = \left( {1 + t} \right){e^{ - t}}$
So, the solution of the differential equation is
\[y\left( {I.F} \right) = \int {\left( {I.F} \right)qdt} \]
$
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = \int {\left( {1 + t} \right){e^{ - t}}\dfrac{1}{{1 + t}}dt} \\
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = \int {{e^{ - t}}dt} \\
$
Now as we know integration of $\int {{e^{ - t}}} = \dfrac{{{e^{ - t}}}}{{ - 1}} + c$ so use this in above equation we have
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = \dfrac{{{e^{ - t}}}}{{ - 1}} + c\] (Where c is some arbitrary integration constant)
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} + c\]……………… (1)
Now it is given that $y\left( 0 \right) = - 1$
So substitute t = 0 and y = -1 in above equation we have,
$
\Rightarrow \left( { - 1} \right)\left( {1 + 0} \right){e^{ - 0}} = - {e^0} + c \\
\Rightarrow - 1 = - 1 + c \\
\Rightarrow c = 0 \\
$
Therefore from equation (1) we have
\[ \Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} + 0\]
\[
\Rightarrow y\left( {1 + t} \right){e^{ - t}} = - {e^{ - t}} \\
\Rightarrow y\left( {1 + t} \right) = - 1 \\
\Rightarrow y\left( t \right) = \dfrac{{ - 1}}{{1 + t}} \\
\]
Now we have to find out the value of y(1)
So put t = 1 in above equation we have,
\[ \Rightarrow y\left( 1 \right) = \dfrac{{ - 1}}{{1 + 1}} = \dfrac{{ - 1}}{2}\]
Hence option (a) is correct.
Note: Whenever we face such types of problems the key concept is to convert the differential equation into standard form in order to evaluate the integrating factor. The integration factor will help us obtain the solution required for the given differential equation.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE